2018
DOI: 10.1002/ece3.4701
|View full text |Cite
|
Sign up to set email alerts
|

The impact of OTU sequence similarity threshold on diatom‐based bioassessment: A case study of the rivers of Mayotte (France, Indian Ocean)

Abstract: Extensive studies on the taxonomic resolution required for bioassessment purposes have determined that resolution above species level (genus, family) is sufficient for their use as indicators of relevant environmental pressures. The high‐throughput sequencing (HTS) and meta‐barcoding methods now used for bioassessment traditionally employ an arbitrary sequence similarity threshold (SST) around 95% or 97% to cluster sequences into operational taxonomic units, which is considered descriptive of species‐level res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 66 publications
3
38
0
Order By: Relevance
“…Our diversity analyses reiterate the impact of sequence similarity levels (cutoffs) on OTU taxonomic composition (Holovachov, Haenel, Bourlat, & Jondelius, 2017;Potter et al, 2017;Tapolczai et al, 2019) since alpha diversity differed when using different cutoffs. The choice of sequence similarity levels greatly depends upon well-curated reference databases, marker of choice, targeted taxa, or a combination of all.…”
Section: Alpha and Beta Diversity In Neotropical Biomesmentioning
confidence: 98%
“…Our diversity analyses reiterate the impact of sequence similarity levels (cutoffs) on OTU taxonomic composition (Holovachov, Haenel, Bourlat, & Jondelius, 2017;Potter et al, 2017;Tapolczai et al, 2019) since alpha diversity differed when using different cutoffs. The choice of sequence similarity levels greatly depends upon well-curated reference databases, marker of choice, targeted taxa, or a combination of all.…”
Section: Alpha and Beta Diversity In Neotropical Biomesmentioning
confidence: 98%
“…In traditional indices, species ecological profiles (optimum and tolerance) are often directly obtained from a large set of data by using simple statistical descriptors of location (e.g., weighted mean) and dispersion (e.g., weighted standard deviation) along a pollution gradient. Interestingly, the morphospecies as a taxonomic unit of the traditional indices can be replaced by molecular taxonomic units, allowing to train a new type of biological indices, the so-called taxonomy-free indices (Apothéloz-Perret-Gentil et al, 2017;Tapolczai et al, 2019). So far, taxonomy-free indices have proved to be an efficient strategy to keep biological information carried by OTUs whose taxonomic assignment is otherwise not possible because of the incomplete reference library.…”
Section: Introductionmentioning
confidence: 99%
“…By considering all the OTUs (or ASVs) profiles along a known impact gradient of typical anthropogenic origin, these studies have shown that HTS data represent a virtually unlimited reservoir of new bioindicators. Examples (listed in Table 1) include contamination by pesticide (Thompson et al, 2016;Andùjar et al, 2017), agriculture stressors (Salis et al, 2017) and gradients of eutrophication and urban contamination (Apothéloz et al, 2017;Martínez-Santos et al 2018;Simonin et al, 2019;Tapolczai et al, 2019aTapolczai et al, , 2019b in freshwater systems. In marine environments, it was demonstrated after an oil spill (Bik et al, 2012), in the vicinity of offshore drilling platforms (Lanzén et al, 2016;Laroche et al, 2016Laroche et al, , 2018a and aquaculture sites (Pochon et al, 2015;Dowle et al, 2015;Stoeck et al 2018aStoeck et al , 2018b as well as along eutrophication and urban or industrial contamination gradients in estuaries (Chariton et al, 2010(Chariton et al, , 2015Angly et al, 2015;Lallias et al, 2015;Obi et al, 2016).…”
Section: The Environmental Genomics Revolution For Biodiversity Reseamentioning
confidence: 99%
“…molecular-based index is directly calibrated on the HTS data, which alleviates the qualitative and quantitative biases encountered with the taxonomy-based EG approaches. Such strategy has proven successful for both freshwater benthic diatoms (Apothéloz et al, 2017;Tapolczai et al, 2019aTapolczai et al, , 2019b and for water bacterial and eukaryotic communities in streams and estuarine systems (Chariton et al, 2015;Li et al, 2018). A strategy analogous to the IndVal approach is the use of polynomial quantile regression splines (Andersson, 2008), which has shown great promise for the prediction of organic enrichment in aquaculture sites using eukaryotic and prokaryotic metabarcoding data in parallel .…”
Section: The Environmental Genomics Revolution For Biodiversity Reseamentioning
confidence: 99%
See 1 more Smart Citation